Peran Mahasiswa Kuliah Kerja Nyata (KKN) dalam Pemanfaatan Bahan Organik Melalui Sosialiasi dan Workshop di Desa Pangauban Kecamatan Pacet Kabupaten Bandung: Pengabdian - Hermawan; Feris Dzaky Ridwan Nafis; Ni’ma Nuzulan Idznillah; Haifa Ersa Salsabila; Faza Syiham Mu’afa; Tegar Wirasatya Al Ashar, K; Lisna Oktaviani; Muhammad Rafli; Nadia Luthfiyanti Zahra; Lidya Fauziyah; Muhammad Fathi Ulumuddin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Pangauban Village, located in Bandung Regency, has a variety of untapped resource potential. This research is a community service report from the Real Work Lecture (KKN) program, which aims to optimize this potential through the application of science and technology to improve community welfare. The main focus of this community service isn on the enviromental, health, and economic sectors. The implementation method includes socialization an workshops. The socialization was held by inviting experienced speakers to present the material, while the workshops were filled with practical activities and direct product creation with the community. This KKN program is an effort to make a real contribution from students to interact and educate the Pangauban Village community directly. This activity includes the transfer of practical knowledge relevant to community needs. The results of this KKN implementation show that student intervention through socialization and workshops is able to significantly increase and expand community knowledge, especially in areas thay are the focus of the program. Active community participation in each session shows how great interest and potential for continued development. In conclusion, this KKN activity has succeeded in being a positive activity that not only provides practical knowledge but also triggers community awareness of the importance of ultilizing local resource for foture enviromental, health, and economic progress.